Low galactic HE gamma-ray blazars in the VVV survey - Pichel, Ana (2015)
Our motivation is to find blazars among the unidentified gamma-ray sources detected with Fermi-LAT in the crowed galactic plane region. Searching for photometric characteristics of blazars in the near- IR using data from the Vista Variables in the Vía Láctea (VVV survey), we aim to find a method to associate blazars to unidentified gamma-ray sources. We show preliminary results on the photometric properties of 4 gamma-ray blazars using the color-magnitude and color-color diagrams. We also compare these results with a different method based on mid-IR observations acquired with Wide-field Infrared Survey Explorer (WISE).